CONTENT MANAGEMENT SYSTEMS (CMS) OPEN SOURCE WEBSITES - Marinela Lăzărică; Florin Dediu (Strategii Manageriale)
Firms need flexible software applications, which may be adaptable to dynamic changes of the modern business environment; they also need more control over their software costs, security and trust in purchased and implemented software. Moreover, they need to be free of individual software vendors and license costs for the software, etc. The solution of this problem consisted in open source applications and open source technology has proven that it can often provide high-quality software being a challenge for old models of software development and maintenance. The first content management system was announced in the late 90s. The offer of such software systems is varied and each of them has its own characteristics. This requires a comparative analysis of viable open-source systems in order to choose the most appropriate imposed goals. In this context, the paper illustrates the use of an open source content management system, like WordPress, to develop a content site in design of websites and analyzeits characteristics.